How Do EFL Students Perceive Challenges Towards Writing Short Drama Script of Narrative Text? - Shabrina Dwi Andani; Frida Unsiah; Agus Gozali (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
The present study aims to find out the dominant challenges experienced by 11th-grade students in writing short drama scripts of narrative text. One hundred six students were involved as research participants. The method used was quantitative descriptive with a questionnaire as the instrument consisting of 15 items about the students' challenges in writing short drama scripts. The questionnaire was distributed to the participants via WhatsApp group, and the teacher researcher asked them to submit it within 20 minutes after it was distributed. The researcher analyzed the participants' results of the questionnaire by using SPSS to find out the mean scores of each item. The mean scores gave information about which items on students' challenges were more dominant. The results show that the students do not experience the challenges of writing short drama scripts because of basic knowledge that the students already have. The willingness of students to read and practice several narrative texts helps increase the students' insight, the use of cooperative learning in class, as well as the readiness and sufficient background knowledge of the teacher to give to the students, are very helpful in developing and writing short drama scripts.